The Antibiotic-Resistant Protein MfpA Modulates Host Cell Apoptosis and Promotes Mycobacterial Survival by Targeting Mitochondria and Regulating the NF-κB Signaling Pathway - Weishan Zhang; Zheng Jiang; Kaixia Mi (Cells)
Mycobacterium tuberculosis (Mtb) is a major global health threat, exacerbated by the emergence of antibiotic-resistant strains. This study investigated fluoroquinolone resistance protein A (MfpA), which enhances mycobacterial survival by targeting host mitochondria and regulating apoptosis. Wild-type (WT) and knockout (KO) Mycobacterium bovis Bacillus Calmette-Guérin (BCG) strains, a common model for Mtb, were utilized to examine host cell responses. Compared to WT strains, KO strains showed reduced colony-forming units (CFUs), elevated TNF-α and IL-6 levels, and increased apoptosis. MfpA was found to localize to mitochondria, increasing ROS production and disrupting mitochondrial membrane potential. Transcriptomic analysis revealed that MfpA modulated the NF-κB signaling pathway, regulating the expression of gadd45β. These results suggest that MfpA drives both antibiotic resistance and virulence by suppressing apoptosis via the mitochondrial and NF-κB pathways, promoting mycobacterial persistence. Studies using BCG provide valuable insight into Mtb’s survival mechanisms, highlighting MfpA’s dual role in resistance and pathogenesis.